A comparison of simultaneously-obtained measures of listening effort: pupil dilation, verbal response time and self-rating. (1st July 2022) - Visentin, Chiara; Valzolgher, Chiara; Pellegatti, Matteo; Potente, Paola; Pavani, Francesco; Prodi, Nicola
Abstract: Objective: The aim of this study was to assess to what extent simultaneously-obtained measures of listening effort (task-evoked pupil dilation, verbal response time [RT], and self-rating) could be sensitive to auditory and cognitive manipulations in a speech perception task. The study also aimed to explore the possible relationship between RT and pupil dilation. Design: A within-group design was adopted. All participants were administered the Matrix Sentence Test in 12 conditions (signal-to-noise ratios [SNR] of −3, −6, −9 dB; attentional resources focussed vs divided; spatial priors present vs absent). Study sample: Twenty-four normal-hearing adults, 20–41 years old ( M = 23.5), were recruited in the study. Results: A significant effect of the SNR was found for all measures. However, pupil dilation discriminated only partially between the SNRs. Neither of the cognitive manipulations were effective in modulating the measures. No relationship emerged between pupil dilation, RT and self-ratings. Conclusions: RT, pupil dilation, and self-ratings can be obtained simultaneously when administering speech perception tasks, even though some limitations remain related to the absence of a retention period after the listening phase. The sensitivity of the three measures to changes in the auditory environment differs. RTs and self-ratings proved most sensitive to changes in SNR.